2017
DOI: 10.1053/j.gastro.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl-CoA Desaturase Promotes Liver Fibrosis and Tumor Development in Mice via a Wnt Positive-Signaling Loop by Stabilization of Low-Density Lipoprotein-Receptor-Related Proteins 5 and 6

Abstract: Background & Aims Stearoyl-CoA desaturase (SCD) synthesizes monounsaturated fatty acids (MUFAs) and has been associated with development of metabolic syndrome, tumorigenesis, and stem cell characteristics. We investigated whether and how SCD promotes liver fibrosis and tumor development in mice. Methods Rodent primary hepatic stellate cells (HSCs), mouse liver tumor-initiating stem cell-like cells (TICs), and human hepatocellular carcinoma (HCC) cell lines were exposed to Wnt signaling inhibitors and changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 42 publications
8
137
0
Order By: Relevance
“…Consistently, three studies published very recently provided various evidence to prove that activation of STING pathway contributes to liver inflammation and the progression of NASH . In addition, we observed that the mRNA of stearoyl‐CoA desaturases 1 ( Scd1 ) was significantly higher in mice with NASH (Figure D), which was consistent with the previous study that overexpression of SCD aggregated while pharmacological inhibitors of SCD attenuated liver fibrosis . We have several more potential targets selected from the transcriptome results are being investigated currently.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistently, three studies published very recently provided various evidence to prove that activation of STING pathway contributes to liver inflammation and the progression of NASH . In addition, we observed that the mRNA of stearoyl‐CoA desaturases 1 ( Scd1 ) was significantly higher in mice with NASH (Figure D), which was consistent with the previous study that overexpression of SCD aggregated while pharmacological inhibitors of SCD attenuated liver fibrosis . We have several more potential targets selected from the transcriptome results are being investigated currently.…”
Section: Discussionsupporting
confidence: 90%
“…[32][33][34] In addition, we observed that the mRNA of stearoyl-CoA desaturases 1 (Scd1) was significantly higher in mice with NASH ( Figure 3D), which was consistent with the previous study that overexpression of SCD aggregated while pharmacological inhibitors of SCD attenuated liver fibrosis. 35 We have several more potential targets selected from the transcriptome results are being investigated currently. Overall, in our view, on one hand, the transcriptome results confirmed the mice with isolated steatosis and NASH model used in this study was the ideal one to study the transition of NASH from isolated steatosis; on the other hand, these findings will give rise to more novel targets for NASH prevention.…”
Section: Bril F Et Al Revealed That Tg Accumulation In Livers Of Patimentioning
confidence: 99%
“…Several evidences suggest that SCD1 is positively relation with a variety of malignant tumors [5456]. A recent study reveals that SCD 1 promotes nuclear localization and transcriptional activity of YAP/TAZ to regulate lung cancer stemness (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…We recently showed that SCD1 is upregulated in CSC-like cell populations compared with non-CSC populations in human liver cancer cell lines [12,13]. Other studies also shed light on the roles of unsaturated fatty acids in maintaining CSC stemness by activating nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) [14] and Wnt-β-catenin [15] signaling pathways. These studies indicate that lipid desaturation is a metabolic signature, and SCD1 may be an important therapeutic target in CSCs.…”
Section: Introductionmentioning
confidence: 99%